Fair Law in Money Laundering with the Origin of Corruption with the Concept of Asset Seizure - Sitompul, Ariman; Aisyah, Aisyah (International Asia Of Law and Money Laundering (IAML), 2024)
Money laundering is a guarantee to get the results of criminal acts establish the economic responsibilities of a country and especially of tact currency exchange rates will be more difficult. Glassy from this, the achievement of assets becomes important because the method of approach used to be known as "following the money". The concept of Internal Revenue money from the perspective of Justice. This study is the norm or research doctrinaire, also referred to as dogmatic research with a conceptual approach and legislation. The study found that the achievement of assets in laundering money has actually been seized in Indonesia in the form of criminal forfeiture based on Criminal Code and code of Criminal Procedure, civil forfeiture and administrative forfeiture under the PPTPPU law, but in setting and implementation there is still a law that can used by criminals to return the proceeds of their crimes, so as not to get a sense of Justice, harming the state and society completely money kidnapping victim. Based on the perspective of Justice derived from the fundamental principle of Justice states that justice should not be contested the culprit. This underlies the need for consideration of regulatory responsibility foreclosure of assets, especially related to civil / in foreclosure rem by reformulating unity in the UU PPTPPU. In addition, liability claims can also be made through legislation that specifically addresses the achievement of assets with a train of thought that is not just limited to the assets in the account user creation service providers only, but includes all assets associated with evil. Maintaining health against certain infectious diseases is also good it needs to be organized to increase the sense of justice for society and the state.